Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1128/msystems.01006-21
|View full text |Cite
|
Sign up to set email alerts
|

The Fecal Microbiome and Metabolome of Pitt Hopkins Syndrome, a Severe Autism Spectrum Disorder

Abstract: GI disturbances in ASD such as severe constipation can be medically significant and often require medication. This is especially true for individuals with PTHS, suggesting that the gut microbiome may be involved in PTHS’s pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…There have also been reported cases of Hirschsprung’s disease in patients with Pitt-Hopkins syndrome 9. Another study has found an altered gut microbiome in patients with Pitt-Hopkins syndrome, as well as the presence of metabolites associated with inflammatory bowel disease 10…”
Section: Discussionmentioning
confidence: 99%
“…There have also been reported cases of Hirschsprung’s disease in patients with Pitt-Hopkins syndrome 9. Another study has found an altered gut microbiome in patients with Pitt-Hopkins syndrome, as well as the presence of metabolites associated with inflammatory bowel disease 10…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium bolteae has been investigated in the context of ASD and is consistently more abundant in these children compared to their NT counterparts 10 , 57 , 58 . Abundances are even higher in individuals with Pitt Hopkins syndrome 59 , a severe ASD with a high incidence of GI dysfunction. C. bolteae produces a conserved specific capsular polysaccharide which is immunogenic in rabbits and has been the focus of ASD vaccine efforts 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous CNTNAP2 deletions have been shown to cause a monogenic disease called Pitt-Hopkins-Like Syndrome 1 (PTHLS1) [ 115 , 116 , 117 ]. PTHLS1 is a rare Mendelian condition characterized by severe intellectual disability, behavioral abnormalities, psychomotor delay along with other symptoms of facial dysmorphism, stereotypic movements, breathing difficulties, and seizures [ 116 ]. Some of these patients also present autism-like behaviors.…”
Section: Discussionmentioning
confidence: 99%